Ability of the Competition Council to Individualize the Fines for Infringement of Article 5 of the Law on Competition - Stelmokaitis, Henrikas (Teisė, 2024)
In 2023, the Description of the Procedure for Setting the Amount of Fines for Infringements of the Law on Competition of the Republic of Lithuania was amended, but the system for setting the amount of the fine remained substantially unchanged. The author seeks to clarify, on the basis of an analysis of case law and arithmetic calculations, whether the Competition Council is able to properly differentiate fines, or whether the existing arithmetic model for calculating the fine excessively restricts the possibilities of differentiation.Neither the Law on Competition nor the Description of the procedure for determining the amount of fines imposed for infringements of the Law on Competition of the Republic of Lithuania contains a clear and consistent methodology for the calculation of fines. The Competition Council‘s resolutions outline the calculation of fines throughout their texts but do not clearly specify the exact mathematical sequence used for determining these fines. Moreover, the Competition Council has a very wide discretion in calculating the basic amount of the fine and does not always avoid logical errors and contradictions. For example, the ‚previous business year‘ often refers to years or even decades prior to the allegedly illegal conduct. The final amount of the fine, even if the gross revenue of the company at the time of the infringement is known, does not guarantee that one could be sure of the maximum amount of the fine, let alone the exact fine for a possible infringement.The analysis of the case law and examples of arithmetic calculations show that when the Competition Council calculates the basic amount of the fine and subsequently applies the coefficients that are mandatory for the calculation of the fine, except for certain extremely rare situations, which are not related to the infringement but rather to the entity‘s choice of differentiation of the portfolio of business activities, the fine to be calculated in accordance with the Description will be the same as the maximum amount provided by the Act.Taking into account the current coefficients in the Description and the arithmetical sequence of steps, it is clear that in the case of agreements between competitors, the fine will most often reach the maximum amount , i.e. above the threshold of 10% of the gross revenue. Accordingly, the Description should be considered contrary to the higher-ranking act, namely Article 36 of the Law on Competition, which mandates the differentiation of fines.